2021
DOI: 10.1186/s12957-021-02266-7
|View full text |Cite
|
Sign up to set email alerts
|

An MR-based radiomics model for differentiation between hepatocellular carcinoma and focal nodular hyperplasia in non-cirrhotic liver

Abstract: Purpose We aimed to develop and validate a radiomics model for differentiating hepatocellular carcinoma (HCC) from focal nodular hyperplasia (FNH) in non-cirrhotic livers using Gd-DTPA contrast-enhanced magnetic resonance imaging (MRI). Methods We retrospectively enrolled 149 HCC and 75 FNH patients treated between May 2015 and May 2019 at our center. Patients were randomly allocated to a training (n=156) and validation set (n=68). In total, 2260 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Among all methods used in the early diagnosis of HCC, radiological examinations, including computerized tomography (CT), magnetic resonance imaging (MRI), and contrast‐enhanced ultrasound (CEUS), are widely used for its noninvasiveness. Based on these examinations, radiomics become a useful tool in the diagnosis and prognosis of liver tumors 4–6 . Compared with CT or MRI, the CEUS has some unique advantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among all methods used in the early diagnosis of HCC, radiological examinations, including computerized tomography (CT), magnetic resonance imaging (MRI), and contrast‐enhanced ultrasound (CEUS), are widely used for its noninvasiveness. Based on these examinations, radiomics become a useful tool in the diagnosis and prognosis of liver tumors 4–6 . Compared with CT or MRI, the CEUS has some unique advantages.…”
mentioning
confidence: 99%
“…Based on these examinations, radiomics become a useful tool in the diagnosis and prognosis of liver tumors. [4][5][6] Compared with CT or MRI, the CEUS has some unique advantages. It can permit real-time imaging and show some rapidly changing features that cannot be detected by CT or MRI.…”
mentioning
confidence: 99%
“…Formerly, many studies have supplied several methods to discriminate against HCC from various BLLs, such as fp-AMLs, FNH, HH and so on [23,24]. It is obvious that most of them analyzed HCC and another benign lesion with rich blood supply by CE-CT/MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the model is internally or externally validated. [76] Radiomics analysis is conducive to the early diagnosis, differential diagnosis, and evaluation of MVI in HCC [77][78][79][80][81][82][83] [Table 3]. Dankerl et al [84] reported that radiomics methods can outperform imaging doctors in predicting the nature of the lesion (benign and malignant), with an accuracy of 75.1%, whereas the range of imaging doctors is between 52% and 74%, depending on their level of experience.…”
Section: Molecular Diagnosis Of Hcc Based On Fine-needle Aspiration (...mentioning
confidence: 99%